Association of the digital clock drawing test with amyloid and tau PET biomarkers in low age risk adults - Huitong Ding; Chenglin Lyu; Cody Karjadi; Preeti Sunderaraman; Christina B. Young; Elizabeth C. Mormino; Spencer Low; Sherral Devine; Katherine Gifford; Rhoda Au; Honghuang Lin (Scientific Reports)
Abstract Although brain amyloid and tau deposition measured by PET scans are established as biomarkers of Alzheimer’s disease (AD), they can emerge decades before symptoms are detectable on traditional neuropsychological (NP) tests. There is a pressing need for early AD detection tools that are more accessible, cost-effective, and non-invasive. The digital clock drawing test (dCDT), a digital version of the clock drawing test, has emerged as a promising cognitive assessment tool that takes minutes to administer and can reveal clinical symptoms earlier than paper–pencil NP tests. This study explored the association between 53 dCDT measures and amyloid and tau PET biomarkers using data from 87 low age risk participants in the Framingham Heart Study. Our findings revealed a significant association between a dCDT measure related to spatial reasoning function and global amyloid burden (P < 0.05), and 4 dCDT measures correlated with tau accumulation after adjusting for multiple comparisons. Notably, the combination of demographic variables and a composite dCDT score achieved a mean area under the receiver operating characteristics curve of 0.86 in detecting amyloid positivity. These results highlight the potential of dCDT measures as effective predictors of amyloid and tau pathology in preclinical AD.